Psychometric Analysis of Attitudes Toward Mathematics Through the Graduated Response Samejima Model - Rodríguez Jiménez, Olga Rosalba (2016)
The assessment of attitudes in education has been used as a tool for preventing the loss of subjects and the desertion. The aim of the study is to perform a psychometric analysis of the “Attitudes towards Mathematics” scale with Samejima´s graded response model (MRG). The sample was of 944 students from different university careers. To analyze the TCT and the MRG model was used. In conclusion, the scale has good psychometric quality. Finally, the benefits of using the MRG for assessing attitudes are presented.